Attachment Security in Infancy Predicts Reduced Parasympathetic Reactivity in Middle Childhood - Tabachnick, Alexandra R. (Attach Hum Dev, 2020)
Children develop physiological regulation in the context of their early attachment relationships. Children with histories of secure attachments during infancy are expected to develop healthier patterns of physiological activity at rest and in response to a stressor than children with insecure attachments. The present study tested this idea by examining the longitudinal associations between infant attachment security and children’s respiratory sinus arrhythmia (RSA) at rest and in response to a frustration task at age 9. The study focused on a sample of children referred from Child Protective Services (N = 97). RSA was selected as the physiological outcome of interest because it reflects the regulation of the parasympathetic branch of the autonomic nervous system, is sensitive to environmental influences, and is associated with emotion regulation. Children who had histories of secure attachments during infancy exhibited less RSA withdrawal during a frustration task than children who had histories of insecure attachments. Attachment security was not significantly associated with baseline RSA. Results suggest that mitigating parasympathetic reactivity during emotionally frustrating situations may be one avenue by which infant attachment security promotes later emotion regulation. Results are discussed in the context of potential avenues for intervention and implications for children exposed to adversity.